Analysis of Sea Surface Temperature Distribution and Its Relation to Rainfall in Pariaman City - Seven, Diko Alafchan; Mubarak, Mubarak; Elizal, Elizal (Jurnal Perikanan dan Kelautan, 2025)
This research was conducted in February 2024. The research locations of Pariaman City waters include Angso Duo Island, Tangah Island, Ujung Island, and Kasiak Island. The research objectives were to determine the distribution of sea surface temperature, average rainfall, and the relationship between sea surface temperature and rainfall. The survey method, direct observation at the research location, was used. The results of this study indicate that the sea surface temperature in the study area in the western season (December - February) ranges from 30.70- 30.430C. The sea surface temperature in the first transitional season (March-May) ranges from 30.06-31.090C. The sea surface temperature in the east season (June - August) ranges from 30.46- 30.90C. The sea surface temperature in the second transitional season (September - November) ranges from 30.08-30.120C. The maximum rainfall in Pariaman City is in the form of rainfall. The maximum rainfall in Pariaman City occurs in November, with an average rainfall of 444 mm, while the minimum rainfall occurs in February, with an average rainfall of 235 mm. The results of the correlation analysis of sea surface temperature with rainfall are weak and strong correlation categories. In March, it produces an "r" value of 0.303, a weak category, and a coefficient of determination (R2) of 0.092 or 9.2%. In October, it produces an "r" value of o.686, a strong category, and a coefficient of determination (R2) of 0.470 or 47%.